PEMETAAN TINDAK KRIMINALITAS DI KOTA PALOPO TAHUN 2015 - Lestari, Alia; Aswad, Muhammad Hajarul (IAIN Palopo, 2016)
Abstract:The crime occurred in Palopo city each year is volatile enough. Although they tend to fallthrough leaving 176 cases in 2013, it does not mean that Palopo is relatively safe from the criminalacts. The societies of Palopo especially the police, it is essential to know the areasincluded in the crime-prone areas. Therefore, this study tried to map the crimes occurred inPalopo city by applying Correspondence Analysis. The research objects were criminal datareported by the police of Palopo City from January to September 2015. From Chi-Squareanalysis, it was found that there was a relationship between the variables of Criminal ActionTypes and Occurrence Time. Similarly, the Criminal Action Types with Occurrence Places, andCriminal Action Types by the reasons occurring Criminal Acts also showed a relationship withcriminal acts against the place and the reasons for the crimes. Furthermore, based on thecorrespondence analysis it was found that the most massive crimes in the area of the police of Palopoare the theft of the motorcycles and the smallest crimes are persecutions. Most of the time incidentsoccurred at 24.00-07.00. The crimes occurred in Wara district.